Worklife Balance, Occupational Health and Safety (K3) and Turnover Intention: Study At PT. Prosperous People of the Archipelago - Mohammad Fariz Satria; Christiantius Dwiatmadja (Budapest International Research and Critics University, 2023)
The research conducted aims to examine the influence of Occupational Safety and Health (K3) and the work-life balance that occurs on turnover intention of millennial employees at PT. Prosperous People of the Archipelago. This study used a total sample of 103 respondents. Purpose sampling is a sampling technique that has the following criteria 1) millennial generation aged 20 to 38 years, 2) Employees working in the production department, and 3) having male and female gender. The analysis technique used in this study is multiple linear regressions. Based on the research that has been done, it can be concluded that in fact work life balance has a negative effect on turnover intention, while K3 has a positive influence on turnover intention. This can be proven by the presence of a sig value smaller than alpha 0.05.